POST-OPERATIVE CHEMOTHERAPY OF RESPIRATORY TUBERCULOSIS IN THE OLDER CHILDREN AND ADOLESCENTS - L. V. Pаnovа; E. S. Ovsyankinа; S. S. Sаdovnikovа; A. Yu. Khitevа (Туберкулез и болезни лёгких)
The article offers criteria defining the duration of post-operative chemotherapy for 3 or 6 months: volume of surgical intervention; degree of inflammation intensity as per data of histopathological examination; detection of growth of mycobacteria of tuberculosis complex in surgical specimens; course of the disease after surgery; chemotherapy tolerance and degree of intensity of remaining changes in the lungs and chest lymph nodes. Basing on the offered criteria, chemotherapy was prescribed to 19 (63.3%) out of 30 patients. Chemotherapy was longer in 9 (30.0%) patients – from 9 to 18 months due to emergency or staging surgery (surgery on two lungs, postponed thoracoplasty) and undulant course of tuberculosis. 2 (6.7%) patients had no chemotherapy due to development of toxic pancreatitis and drug-induced anemia.